Love of Money, Religiosity, and Tax Understanding on Tax Evasion - Agus Fuadi; Dian Sulistyorini Wulandari; Dian Sukma Lestari (East Asian Journal of Multidisciplinary Research, 2023)
This study aims to determine the effect of Love of Money, religiosity, and Tax Understanding on the act of tax evasion by individual taxpayers registered at KPP Pratama Cikarang Selatan. The source of data in this study is primary data, which in this study is obtained from the results of distributing questionnaires to a predetermined sample of taxpayers registered at KPP Pratama Cikarang Selatan. The secondary data in this study comes from written sources published by third parties, such as literature, previous research, journals, and other information related to research. Sampling used convenience random sampling, with a sample of 100 taxpayers registered at KPP Pratama Cikarang Selatan (The year 2021). Data analysis used multiple regression analysis. The results showed that partially, Love of Money, religiosity, and Tax Understanding had a positive and significant effect on Tax evasion, and simultaneously, Love of Money, religiosity, and Tax Understanding had a positive and significant impact on Tax evasion.